The Coordination of Foreign R&D Activities by Transnational Corporations - Fischer, William A.; Behrman, Jack N. (Journal of International Business Studies, 1979)
The nature of coordination of practices between the headquarters and field operations has long been a matter of considerable importance to the management of research and development (R&D). When the firm performs R&D aboard, in foreign locations, the issue of coordination increases in significance. This article reports on interviews with 35 American and 18 European transnational corporations regarding the coordination of their foreign R&D activities. Coordination practices are shown to affect the nature of R&D performed aboard, the means of establishing R&D aboard, the communication and control systems employed, and the patterns of invention and innovation.